1985
DOI: 10.7863/jum.1985.4.9.479
|View full text |Cite
|
Sign up to set email alerts
|

Placental thickness.

Abstract: The sonograms of 200 randomly selected singleton pregnancies were reviewed. Placental thickness was measured and correlated with menstrual age. The placenta was demonstrated to increase in thickness with advancing menstrual age. At no stage of pregnancy was the normal placenta greater than 4 cm in thickness. Potential pitfalls in measuring placental thickness are addressed, as well as potential causes of aberrations in placental thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
59
0
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(69 citation statements)
references
References 2 publications
7
59
0
3
Order By: Relevance
“…Historically, a placenta of greater than 4 cm in thickness has been regarded as abnormal and associated with various poor outcomes. [4][5][6] However, the ratio of the birth weight to the placental weight has been used since the 1940s as an index for the appropriateness of fetal growth and there are no current data to support this cutoff value or specifically addressing placental thickness in all trimesters of gestation. As such, few studies have been done to correlate placental thickness with the fetal weight.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, a placenta of greater than 4 cm in thickness has been regarded as abnormal and associated with various poor outcomes. [4][5][6] However, the ratio of the birth weight to the placental weight has been used since the 1940s as an index for the appropriateness of fetal growth and there are no current data to support this cutoff value or specifically addressing placental thickness in all trimesters of gestation. As such, few studies have been done to correlate placental thickness with the fetal weight.…”
Section: Introductionmentioning
confidence: 99%
“…Tem-se dado importância também à espessura placentária pela sua relação com a presença de infecções materno-fetais e com a idade gestacional 5 . A espessura placentária é obtida por meio da medida a partir da placa basal até a placa corial, no ponto da inserção do cordão umbilical.…”
Section: Palavras-chave: Placenta Gravidez Normal Ultra-sonografiaunclassified
“…This is due to increase in placental thickness with gestational age. [3] Several studies have reported an increase the placenta thickness with gestational age. The Studies reported by [4][5][6] It was observed that the placenta thickness gradually increased from 11 weeks of gestation to 39 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…It is technically defined as the apposition or fusion of fetal organs to maternal tissue for the purpose of physiologic exchange. [3] The placenta thickness appears to be promising parameter for estimation of gestation of intra uterine fetus age. This is due to increase in placental thickness with gestational age.…”
Section: Introductionmentioning
confidence: 99%